Real-time Environmental Applications and Display sYstem: READY. (September 2017) - Rolph, Glenn; Stein, Ariel; Stunder, Barbara
Abstract: Air quality forecasters, emergency responders, aviation interests, government agencies, and the atmospheric research community are among those who require access to tools to analyze and predict the transport and dispersion of pollutants in the atmosphere. Because of this need, the unique web-based Real-time Environmental Applications and Display sYstem (READY) has been under continuous development since 1997 to provide access to a suite of tools for producing air parcel trajectory and dispersion model results and displaying meteorological data. READY provides a "quasi-operational" portal to run the HYSPLIT atmospheric transport and dispersion model and interpret its results. Typical user applications include modeling the release of hazardous pollutants and volcanic ash, forest fire and prescribed burn smoke forecasting, poor air quality events, and various climatological studies. In addition, READY provides the user with quick access to meteorological data interpolated to the location of interest, helping in the interpretation of the HYSPLIT model results. Highlights: Unique web-based system for running the HYSPLIT atmospheric transport and dispersion model. Meteorological display tools for analyzing the meteorological data using in HYSPLIT. For air quality forecasters, emergency responders, government agencies, atmospheric research and aviation community.